2006
DOI: 10.4161/psb.1.6.3511
|View full text |Cite
|
Sign up to set email alerts
|

The Root Apex ofArabidopsis thalianaConsists of Four Distinct Zones of Growth Activities

Abstract: In the growing apex of Arabidopsis thaliana primary roots, cells proceed through four distinct phases of cellular activities. These zones and their boundaries can be well defined based on their characteristic cellular activities. The meristematic zone comprises, and is limited to, all cells that undergo mitotic divisions. Detailed in vivo analysis of transgenic lines reveals that, in the Columbia-0 ecotype, the meristem stretches up to 200 microm away from the junction between root and root cap (RCJ). In the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
165
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 264 publications
(174 citation statements)
references
References 124 publications
3
165
0
Order By: Relevance
“…1A; Verbelen et al, 2006). We found that cells in the meristem and cap displayed a Ca 2+ -dependent increase in FRET efficiency in response to Glu and ATP that had similar shapes as those observed in the transition zone (Fig.…”
Section: Imaging Of Fret-sensitized Emission Allows Monitoring Of [Casupporting
confidence: 57%
See 2 more Smart Citations
“…1A; Verbelen et al, 2006). We found that cells in the meristem and cap displayed a Ca 2+ -dependent increase in FRET efficiency in response to Glu and ATP that had similar shapes as those observed in the transition zone (Fig.…”
Section: Imaging Of Fret-sensitized Emission Allows Monitoring Of [Casupporting
confidence: 57%
“…1A, white rectangular box). This region of the root has been referred to as the distal elongation zone or transition zone and is one of the proposed four distinct zones in the Arabidopsis primary root that has characteristic cellular activities (Verbelen et al, 2006). We chose this region for our initial Ca 2+ -dependent FRET efficiency measurements because it has been shown to be the most responsive to various environmental stimuli (Baluška et al, 2001;Verbelen et al, 2006).…”
Section: Fret-sensitized Emissionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 As cells acquire their final length in growth terminating zone, the newly deposited microfibrils are no more strictly transverse and thereby cortical microtubules are reoriented. 18 The supply of newly synthesized microfibrils has to keep pace with wall expansion throughout cell elongation.…”
Section: E1028701-2mentioning
confidence: 99%
“…In particular, the apical part (distal) of this region seems to be characterized mainly by cells that optionally can reenter the cell cycle, whereas cells of the basal (proximal) part of this zone are able to readily enter into the fast cell elongation region. 42,44,45 This developmental feature could be differentially regulated at the opposite root flanks, providing the root apices with an effective mechanism to re-orientate growth in response to environmental stimuli. 44 The transition zone is a unique zone being competent for integration of diverse endogenous and exogenous signals, and translating them into adaptive differential growth responses.…”
Section: The Root Transition Zonementioning
confidence: 99%